A produção literária de Altamirando Requião: a Bahia do século XVII em O Baluarte - Melo, Cristiane Tavares Santos (2013)
Contemporary of Jorge Amado, Carlos Chiacchio, Rui Barbosa, Afrânico Peixoto, among others, Altamirando Requião devoted himself to poetry and novel, but his performances in the journalism and in the politc end up taking the most part of his activities. He was owner of newspaper Diário de Notícias and acted too how collaborator in other newspapers and magazines of Bahia and Rio de Janeiro, where he published many articles and essays. The current work proposes to study the cultural memory of Bahia in the century XVII, through of novel O Baluarte (1976). We also will use some texts from owner author, published in journals such as subsidy to analyze the novel. For this, firstly, we will get the authot back, placing his cultural moment of production and contribution for the literary production of Bahia. We will take advantage of opportunity for analyze the fact of the suppression of artistic identities, such as Requião that, in spite of be one of the members founders of Academia de Letras da Bahia and to be in the center of intellectual production from Bahia,too, he didn’t get write his name in the official historiography in literary critical. Then we will analyze the work O Baluarte (1976), through of relations between literature and history.